Optimization Of The Authority Of Civil Servant Investigators (PPNS) In The Directorate General Of Taxes (DGT) Bangka Belitung Region In The Seizure And Blocking Of Suspect Assets For The Recovery Of State Revenue Losses - Yunita Dwi Yanti; Muhamad Adystia Sunggara (Green Publisher Indonesia, 2024)
Tax crimes have become a significant issue in Indonesia, as taxes are vital for the government's development efforts. Failure to comply with tax obligations not only impacts the state's revenue but also hinders the equitable distribution of welfare to society. The purpose to be achieved in this study is to find out related to the authority of PPNS in the seizure and blocking of suspect assets in order to recover losses in state revenue. The method used in this study is empirical juridical where the data obtained through primary data by interviewing the DGT Bangka Belitung region. In addition, secondary data is also used to add information and strengthen the analysis related to the research topic. The results showed that the recovery of State losses can be done by the DGT where the authority can be done by confiscation and blocking of assets. This mechanism is carried out with the aim that the country does not suffer considerable losses. Tax investigation collection is one of the actions that can reduce tax crimes so that the activities carried out must be carried out efficiently in accordance with applicable regulations